Sudden death syndrome of soybean under different soil management systems and cover crops - Reis, Emerson Fábio dos; Pelissari, Adelino; Moraes, Anibal; Oliveira, Edilson Batista de; Ruaro, Lucimeris (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to assess the effect of soil management systems and winter cover crops on the number of propagules of Fusarium spp. in soil, the incidence of sudden death syndrome (SDS), and the productivity of the soybean cultivars CD 206 and FT Fênix. Two experiments were carried out in the 2006/2007 and 2007/2008 crop years. The experimental design was a randomized complete block in a split‑split plot arrangement, with three replicates. Two soil tillage systems were evaluated: no‑tillage and plowed soil at a depth of 25 cm. The soil covers used were: black oat, with two planting densities; black oat + vetch; ryegrass; and fallow. The incidence of the disease in the 2006/2007 crop year in the cultivar FT Fênix was lower than in CD 206. In the 2007/2008 crop, there was no significant difference. There was an increase in productivity, of 125 kg ha-1, in the plowed treatment, when compared to no‑tillage. The cover with black oat + vetch showed a higher number of propagules of Fusarium spp. in soil in the 2006/2007 crop year. However, in the second year, this difference was not observed. The soil management systems and winter cover crops used do not influence the incidence of SDS in soybean cultivars or the number of Fusarium spp. propagules in soil. The plowed system provides an increase in soybean yield in the second year of management.